2013
DOI: 10.1097/sap.0b013e3182a0df25
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Readmission After Breast Reconstruction

Abstract: This is the first study of readmission rates after breast reconstruction. Knowledge of specific risk factors for readmission may improve patient outcomes, steer strategies for optimizing reconstructive outcomes, and minimize readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 38 publications
1
17
1
Order By: Relevance
“…In contrast to previous studies, we found no associations between age, BMI, or duration of operation and SSI rates [1,2,7,15,21,36]. Our SSI rate, of 4.5%, was also relatively low.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies, we found no associations between age, BMI, or duration of operation and SSI rates [1,2,7,15,21,36]. Our SSI rate, of 4.5%, was also relatively low.…”
Section: Discussioncontrasting
confidence: 99%
“…Most hospital readmissions after surgery are due to SSI [1]. With the recent focus on readmission rates as an indicator of quality of care, to minimize the risk of patient readmission after surgery is imperative [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of ADM remodeling in prosthetic breast reconstruction is derived from clinical experience 54, 55 , translational animal models 53, 5658 , and extrapolation from the hernia literature 48, 59 . Remodeling of an ADM sandwiched between well-vascularized surfaces 6062 is expected to be more robust than around a prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Past research on the association between smoking status and readmission rates has produced equivocal results. [26][27][28][29][30][31][32][33][34] Many studies have examined commonly collected demographic variables. It has been reported that increasing age could potentially serve as a predictor of all-cause hospital readmissions, especially in patients over the age of 65.…”
Section: Discussionmentioning
confidence: 99%